Laboratory study of water absorption of modified mortar - Borhan, M.M; Norsuzailina, Mohamed Sutan (UNIMAS Publisher, 2022)
This study investigates the effects of polymer additives namely polyvinyl acetate (PVAc) on water absorption and compressive strength of mortar. Twelve mortar mixtures were investigated for water absorption test and compressive strength test. Results showed that water absorption were inversely proportional to the percentage of PVAc addition. Final analysis showed that addition of PVAc had significant effects on water absorption. Samples with 1%, 3% and 5% addition of PVAc showed an increase of water absorption capacity in comparison to control mortar.